2019
DOI: 10.3389/fimmu.2019.00515
|View full text |Cite
|
Sign up to set email alerts
|

Immune Cell Profiling of the Cerebrospinal Fluid Provides Pathogenetic Insights Into Inflammatory Neuropathies

Abstract: Objective: Utilize immune cell profiles in the cerebrospinal fluid (CSF) to advance the understanding and potentially support the diagnosis of inflammatory neuropathies. Methods: We analyzed CSF cell flow cytometry data of patients with definite Guillain-Barré syndrome (GBS, n = 26) and chronic inflammatory demyelinating polyneuropathy (CIDP, n = 32) based on established diagnostic criteria in comparison to controls with relapsing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 45 publications
0
30
0
1
Order By: Relevance
“… 30 Furthermore, a recent study on the CSF of patients with inflammatory neuropathies revealed a distinctive increase in NK cell numbers—indicating an underestimated role of NK cells in inflammatory neuropathies. 31 …”
Section: Discussionmentioning
confidence: 99%
“… 30 Furthermore, a recent study on the CSF of patients with inflammatory neuropathies revealed a distinctive increase in NK cell numbers—indicating an underestimated role of NK cells in inflammatory neuropathies. 31 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, peripheral blood CD8 + T cells from patients with CIDP have extensive oligoclonal expansion compared with CD4 + T cells. More recently, we found that CSF composition of patients with CIDP is disease specific, with a significant increase in cytotoxic cell types NKT cells and CD8 + T cells (45,46). In mouse CIDP models, the role of CD8 + T cells requires further clarification.…”
Section: Immune Effectors In Cidpmentioning
confidence: 94%
“…Histology (33,45,69) and electron microscopy (70, 71) on nerve biopsies from patients with CIDP has provided important information about CIDP pathogenesis. A deeper understanding of molecular mechanisms was gained by FACS analysis of patient blood (72) and CSF (46,72). Notably, transcriptomic technologies are beginning to reveal a much higher resolution view of the cellular composition of the PNS in homeostasis and CIDP disease development.…”
Section: Emerging Approaches To Understanding Human Cidpmentioning
confidence: 99%
“…For example, missense loss-of-function mutations in perforin have been identified in some CIDP patients (Buttini et al, 2015), and a study of 22 CIDP patients and 22 healthy controls showed the proportion of CD3 − CD56 + NK cells was lower in the blood of patients (Sanvito et al, 2009). CSF from inflammatory neuropathy patients contains elevated NK cells in association with GBS, whereas CD8 + T and CD3 + NKT cells levels were increased in CIDP patients (Heming et al, 2019). These findings suggest that heterogeneity in the cytotoxic cellular immune response could play role in differentiating the acute and chronic forms of inflammatory peripheral neuropathy.…”
Section: Cellular Immunity In Inflammatory Neuropathiesmentioning
confidence: 99%